Nutrient and Metabolic Sensing in T Cell Responses - Wei, Jun; Raynor, Jana; Nguyen, Thanh-Long M.; Chi, Hongbo (Frontiers in Immunology, 2017)
T cells play pivotal roles in shaping host immune responses in infectious diseases, autoimmunity and cancer. The activation of T cells requires immune and growth factor-derived signals. However, alterations in nutrients and metabolic signals tune T cell responses by impinging upon T cell fates and immune functions. In this review, we summarize how key nutrients, including glucose, amino acids and lipids, and their sensors and transporters shape T cell responses. We also briefly discuss regulation of T cell responses by oxygen and energy sensing mechanisms.